The Particularities Of Auditory Performance Evaluation In Bimodal Hearing Rehabilitation – Cochlear Implant And Hearing Aid - Raluca Olariu; Luminita Radulescu; Gabriela Damean; Cristian Martu; Sebastian Cozma (Romanian Journal of Oral Rehabilitation, 2012)
Introduction Cochlear implantation is the standard intervention for hearing and speech rehabilitation of the patients with bilateral severe and profound hearing loss. The concomitant usage of a hearing aid in the contralateral ear offers a better sound localization and speech understanding in complex noise situation. Materials and methods The study group included twelve patients, adults and children, implanted in our cochlear implant centre, who still wear a hearing aid in the opposite ear. For all the subjects we considered the age at the implantation, the aetiology and the onset of the hearing loss, pre- and postimplantation audiological evaluation with the cochlear implant and with the hearing aid. Results The free field pure tone thresholds with the cochlear implants are superior to those with the hearing aid in the opposite ear. The cochlear implant offers a better audition for the high frequencies comparing to the reverse situation of the hearing aid. Discussions: The particularity of the auditory performance evaluation in bimodal rehabilitated patients – cochlear implant in one ear and hearing aid in the opposite ear is represented by the necessity to create a particular audiological evaluation algorithm adapted to that situation. Conclusions The results of the present study suggest an advantage of cochlear implant usage in conjunction with a hearing aid in the opposite ear. The cochlear implant alone performs better than the hearing aid alone, and the bimodal condition is superior to the cochlear implant alone. The bimodal hearing rehabilitation requires a regularly auditory re-evaluation to establish the limit line between the benefit / less benefit of bimodal hearing.